Gambaran Pengelolaan Penyimpanan Obat di Gudang Farmasi Rumah Sakit Pemerintah Provinsi Riau Tahun 2018 - Erniza Pratiwi; Wulan Sari Firmes Putri; Husnawati Husnawati (Universitas Borneo Lestari, 2022)
Storage is an activity of storing and maintaining by placing drugs and medical supplies received in a place that is considered safe from theft and physical disturbances that can damage the quality of drugs and health supplies. Hospital is a social and medical organization whose function is to provide comprehensive health services to the community. This study aims to see a description of the management of drug storage in the pharmacy warehouse of the Riau Provincial Government Hospital in accordance with the Guidelines for Pharmaceutical Management Training Materials at the Regency/City Pharmacy Installation. This research is a descriptive observational research and data collection is done in a cross sectional manner by filling out checklist sheets and free guided interviews. The samples in this study were pharmacy and drug warehouses, as well as pharmacy staff (in charge) who were directly related to the drug storage warehouse at the Riau Provincial Government Hospital. The results obtained indicate that the requirements for warehouse and stock recording have met the requirements while the storage / preparation of drugs has not met the requirements. Drug warehouse requirements with a percentage of 90% (very good), requirements for storage / preparation of drugs with a percentage of 72.73% (good) and requirements for a drug stock recording system with a percentage of 100% (very good).